2022
DOI: 10.1161/circinterventions.121.011489
|View full text |Cite
|
Sign up to set email alerts
|

Economic Considerations in Access to Transcatheter Aortic Valve Replacement

Abstract: Transcatheter aortic valve replacement (TAVR) has revolutionized the treatment of aortic stenosis, with the number of procedures and sites offering the procedure steadily rising over the past decade in the United States. Despite this, growth into certain markets has been limited as hospitals have to balance high TAVR costs with the ability to offer a complete array of state-of-the-art therapies for aortic stenosis. This trade-off often results in decreased access to TAVR services by patients cared for in hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Drug‐eluting stents and TAVR, for example, have diffused faster in markets with higher degrees of competition between cardiology practices. 20 , 21 However, prior work has found that even within large, urban health systems where access to care is not geographically limited, Black and White patients may have differing attitudes toward medical innovation. This may be informed by socioeconomic factors and trust in the health care system and may explain differing propensities to accept novel, invasive treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Drug‐eluting stents and TAVR, for example, have diffused faster in markets with higher degrees of competition between cardiology practices. 20 , 21 However, prior work has found that even within large, urban health systems where access to care is not geographically limited, Black and White patients may have differing attitudes toward medical innovation. This may be informed by socioeconomic factors and trust in the health care system and may explain differing propensities to accept novel, invasive treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Volume requirements and mandatory ancillary services are implemented to ensure quality of outcomes, but recent research provides conflicting evidence on the utility of volume requirements as surrogates for quality. 2 Thus, regulatory agencies must strike the challenging balance of maintaining procedural quality while also providing equitable access to these high-technology procedures. Site-level administrative burdens may hamper decentralization of structural heart services to smaller community hospitals.…”
mentioning
confidence: 99%
“…These inequities arise from various factors, including structural racism, and are shaped by the intersectionality of environmental, legal, and social elements . Historically, there has been decreased application of novel cardiovascular therapies among patients who are Black or Latinx or from socioeconomically disadvantaged groups . Consistent with reduced access to cardiovascular therapies, previous work has found associations of race, ethnicity, and socioeconomic status with reduced use of structural heart disease interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Many of the improvements in TAVR efficiency have been successful at chipping away at the remaining hospital costs allowing efficient hospitals adopting these practices to realize a modest contribution margin from their TAVR programs. 14 However, if outpatient coding that reimburses significantly lower than current inpatient diagnosis-related group codes were to emerge for TAVR, this would actually be counterproductive to hospital finances despite the perceived efficiencies created by SDD. This could well exacerbate the already existing inequities in access to TAVR faced by rural, minority, and socioeconomically disadvantaged populations.…”
mentioning
confidence: 99%